2022
DOI: 10.3390/ijms23052620
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Entry Inhibitors Discovered from Maesa perlarius

Abstract: Ebola virus disease (EVD), a disease caused by infection with Ebola virus (EBOV), is characterized by hemorrhagic fever and a high case fatality rate. With limited options for the treatment of EVD, anti-Ebola viral therapeutics need to be urgently developed. In this study, over 500 extracts of medicinal plants collected in the Lingnan region were tested against infection with Ebola-virus-pseudotyped particles (EBOVpp), leading to the discovery of Maesa perlarius as an anti-EBOV plant lead. The methanol extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Dimeric PAC and several flavan-3-ol monomers within this extract were found to be potent EBOV entry inhibitors at low micromolar concentrations. By docking analysis and microscale thermophoresis technology, the authors determined that these compounds exhibited virucidal potency by interacting with EBOV glycoprotein, and the most efficient antiviral compound was the PAC-B2 [ 259 ].…”
Section: The Broad-spectrum Antiviral Activity Of A-type Pacsmentioning
confidence: 99%
“…Dimeric PAC and several flavan-3-ol monomers within this extract were found to be potent EBOV entry inhibitors at low micromolar concentrations. By docking analysis and microscale thermophoresis technology, the authors determined that these compounds exhibited virucidal potency by interacting with EBOV glycoprotein, and the most efficient antiviral compound was the PAC-B2 [ 259 ].…”
Section: The Broad-spectrum Antiviral Activity Of A-type Pacsmentioning
confidence: 99%
“…The bioactive procyanidins are known for their ample benefits to human health and have been shown to have a plethora of biological effects [ 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The bioactive effects of procyanidins in general, PC1 in particular, could be ascribed to their capability to localize in the biological membrane and to modulate the membrane structure and/or the dynamics, as well as their interaction with the lipids and proteins [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the quantity of procyanidins is very high in vegetables, fruits, cereals, and the seeds of numerous species of plants [ 2 , 4 ] and they are very heterogeneous compounds with a diverse chemical structure [ 5 , 6 ]. Most importantly, they have been shown to possess a plethora of valuable properties, which include anticarcinogenic, antimicrobial, antiviral, antiinflammatory, antiallergic, antimutagenic, and antihyperglycaemic effects [ 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (400 MHz, CD 3 OD) δ 7.59− 7.55 (m, 2H), 7.51 (d, J = 8.3 Hz, 1H), 7.32 (dt, J = 8.4, 1.5 Hz, 1H), 6.84 (d, J = 1.0 Hz, 1H), 6.52 (dd, J = 2.3, 0.9 Hz, 1H), 5.78 (s, 2H). (34). To a solution of 4g (46.5 mg, 135 μmol) in dry DMF (3.00 mL/mmol) cooled to 0 °C, DIPEA (5.00 equiv, 676 μmol) and HATU (2.00 equiv, 271 μmol) were added sequentially.…”
Section: -(4-chloro-3-(trifluoromethyl)benzyl)-4h-furo[32-b]pyrrole-5...mentioning
confidence: 99%
“…More work is needed for small molecules that target entry. Structure−activity relationship studies have identified benzamides, 32 adamantane carboxamides, 33 and proanthocyanidins 34 that display potent activity against EBOV; however, additional characterization against other filoviruses has not been reported. In contrast, a ridaifen-B analogue, XL-147, displayed favorable broad-spectrum antifiloviral activity, yet off-target effects at the estrogen receptor need to be addressed before further advancement.…”
Section: ■ Introductionmentioning
confidence: 99%